Implementasi Media Komik dalam Meningkatkan Ketrampilan Menulis Puisi Siswa MI Al-Hidayah - Hakim, Nur; Sholihah, Iqlimatus (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
The purpose of this study was to find out how the implementation of comics media in improving students' poetry writing skills. This study uses a descriptive qualitative research approach, while the type of research is a case study research using research instruments, namely the researchers themselves and using observation, interview, and documentation research data mining techniques. The data analysis model used is the Miles and Huberman Interactive model, which consists of three stages. First data collection, second data reduction, third data presentation/data display and verification or conclusion. Data analysis was carried out continuously until the end of the study. The subject of the study was the students of MI Al-Hidayah Serah Panceng Gresik. The respondents in this study amounted to 24 students. The independent variables of this study were the implementation of comics and media, while poetry writing skills were the dependent variable. The results of this study indicate that the implementation of comics media is very effective in improving the poetry writing skills of MI AL-Hidayah students for the 2020-2021 academic year.